Affective Meaning in the Jakarta Globe Articles: Semantic Analysis - Muhammad Yusuf; Salsabilla, Dinda (Linguistik, Terjemahan, Sastra (LINGTERSA), 2023)
The research's objective was to identify the categories of affective meaning utilized within environmental news articles published by The Jakarta Globe. The data for this study was sourced from online articles published in The Jakarta Globe's June 2022 edition. The research employed a qualitative content analysis approach. Data collection involved gathering information from the website https://jakartaglobe.id/tag/?tags=environmentÂ and extracting news articles from The Jakarta Globe. The analysis focused on the content of these online articles. The findings of the study revealed the presence of affective meanings expressed as positive and negative emotions. The study gathered 19 instances of affective meaning, comprising 8 instances of positive affective meaning and 11 instances of negative affectiveÂ meaning.